Cloning and sequence analysis of the rpsL and rpsG genes of Mycobacterium smegmatis and characterization of mutations causing resistance to streptomycin. - Kenney, T J (1994)
The Mycobacterium smegmatis rpsL and rpsG genes, encoding the ribosomal proteins S12 and S7, were cloned, and their DNA sequence was determined. The third nucleotide of the S12 termination codon overlapped the first nucleotide of the S7 translation initiation codon. A collection of 28 spontaneous streptomycin-resistant mutants of M. smegmatis were isolated. All had single-base-pair substitutions in the rpsL gene which were changed to a streptomycin-sensitive phenotype by complementation with a low-copy-number plasmid carrying the wild-type M. smegmatis rpsL gene. A total of eight different mutations were found in two specific regions of the rpsL gene. Fifty-seven percent (16 of 28) altered the Lys codon at position 43. Forty-six percent of the mutations (13 of 28) were due to a transition changing an AAG Lys codon to an AGG Arg codon, with eight changes at codon 43 and five at codon 88.